2014
DOI: 10.1212/wnl.0000000000000908
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the IL-23/IL-17 axis and myeloid factors in secondary progressive MS

Abstract: The results of this exploratory study raise the possibility that Th17 responses and IL-17-inducible myeloid factors are elevated during SPMS compared with RRMS, and correlate with lesion burden. Our data endorse further investigation of Th17- and myeloid-related factors as candidate therapeutic targets in SPMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…6A). Cerebral MRI scans were obtained from each subject and analyzed as previously described [17]. Average MRI T2 lesion load was similar across the three groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6A). Cerebral MRI scans were obtained from each subject and analyzed as previously described [17]. Average MRI T2 lesion load was similar across the three groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PBMCs were isolated using CPT Vacutainer tubes (Fisher Scientific), suspended in fetal bovine serum with 20% dimethyl sulfoxide, and stored in liquid nitrogen until thawed for analysis. ELISPOT assays were performed to enumerate the frequencies of MBP-specific IFNγ and IL-17 producers, using a protocol that we previously described [17]. Subjects were classified as IFNγ-skewed if the frequency of MBP-specific IFNγ producers in their PBMC exceeded that of IL-17 producers by two-fold or more in at least two thirds of samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies reported increased activation of peripheral blood immune cells from progressive patients, while pathology studies indicate that in SP and PP the inflammation is abundant, widespread and diffuse in CNS, and correlates with axonal damage and disease progression (42). A crucial role of IL-17 and of dysregulation of the IL-23/IL-17 axis in the blood of SP patients, and a correlation between the levels of these pro-inflammatory factors, the lesion load at MRI and brain atrophy have been recently documented (43, 44). Studies in experimental autoimmune encephalitis animal models showed that myelin-reactive Th17 cells induces ectopic follicles in the CNS (45), and this seems particularly intriguing in light of the discovery of lymphoid follicle-like structures in the meninges and in the large perivascular space of CNS of SP patients’ brain specimens, supporting the hypothesis of a compartmentalization of, and sustained inflammation in the CNS of progressive stages of MS (46, 47).…”
Section: Discussionmentioning
confidence: 99%